2020
DOI: 10.1155/2020/8458257
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons in Surface Water from Wuhai and Lingwu Sections of the Yellow River: Concentrations, Sources, and Ecological Risk

Abstract: In this study, concentrations, sources, and ecological risk of 16 polycyclic aromatic hydrocarbons (PAHs) in 41 surface water samples collected from Wuhai and Lingwu sections of the Yellow River were investigated. The results showed that total PAH concentrations varied from 27.5 ng/L to 234 ng/L and from 135 ng/L to 265 ng/L in surface water of Wuhai and Lingwu sections, respectively. Source identification was performed by using principal component and multiple linear regression analysis. PAHs in Wuhai section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Table 2 shows the concentration ranges of PAHs found in several rivers around the world. The comparison showed that the amount of ΣPAHs in the sediment samples (434.8–872.1 ng g −1 ) was similar to those found in the Yellow River, China [ 50 ], in the Erjien River, Taiwan [ 60 ], and was greater than the concentration found in the East China Sea, China [ 61 ], in the Yellow River and in the Henan Reach of Yellow River, China [ 44 , 56 ], in the Yellow River Estuary, China [ 62 ], in the Danube River, Hungary [ 57 ],and in Italy, in the Tiber River [ 34 , 48 , 63 ] and in the Sarno River [ 26 ]. However, the amount of ΣPAHs in the sediment samples was lower than the concentration found in the Daliao River, China [ 49 ], in the Cocó and Ceará Rivers, Brazil [ 64 ], in the Cauca River, Colombia [ 8 ], in the Buffalo River Estuary, South Africa [ 55 ], in the Ammer River, Germany [ 9 ], and in Durance River and Huveaune River, France [ 65 , 66 ].…”
Section: Resultssupporting
confidence: 62%
“…Table 2 shows the concentration ranges of PAHs found in several rivers around the world. The comparison showed that the amount of ΣPAHs in the sediment samples (434.8–872.1 ng g −1 ) was similar to those found in the Yellow River, China [ 50 ], in the Erjien River, Taiwan [ 60 ], and was greater than the concentration found in the East China Sea, China [ 61 ], in the Yellow River and in the Henan Reach of Yellow River, China [ 44 , 56 ], in the Yellow River Estuary, China [ 62 ], in the Danube River, Hungary [ 57 ],and in Italy, in the Tiber River [ 34 , 48 , 63 ] and in the Sarno River [ 26 ]. However, the amount of ΣPAHs in the sediment samples was lower than the concentration found in the Daliao River, China [ 49 ], in the Cocó and Ceará Rivers, Brazil [ 64 ], in the Cauca River, Colombia [ 8 ], in the Buffalo River Estuary, South Africa [ 55 ], in the Ammer River, Germany [ 9 ], and in Durance River and Huveaune River, France [ 65 , 66 ].…”
Section: Resultssupporting
confidence: 62%
“…These foundational techniques are further augmented by HPLC interfaced with diode-array and fluorescence detection (HPLC-DAD-FLD) as well as HPLC linked with fluorescence and ultraviolet detection (HPLC-FLD-UV). Although these supplementary methods are utilized less frequently, they offer invaluable spectral data and heightened sensitivity for detecting certain PAH compounds under specific analytical conditions [248][249][250][251]. GC-MS is particularly noteworthy for its superior sensitivity, selectivity, and operational efficiency, which positions it as the method of choice for analyzing volatile and semi-volatile organic compounds, including PAHs.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…Then, 20 μl of injection standards (10 μg/ml HMB) was added to prepare the final volume of 1 ml in dichloromethane for instrumental analysis. 20…”
Section: Pretreatment Analysismentioning
confidence: 99%